2018
DOI: 10.1098/rsos.171782
|View full text |Cite
|
Sign up to set email alerts
|

The evolution and anatomy of the horse manus with an emphasis on digit reduction

Abstract: We revisit digit reduction in the horse and propose that all five digits are partially present in the modern adult forelimb. Osteological descriptions of selected tetradactyl, tridactyl and monodactyl equids demonstrate the evolution of the forelimb. Histological, osteological and palaeontological evidence suggest that the Equus distal forelimb is more complex than traditionally conceived. The current understanding is that the horse distal forelimb consists of one complete digit (III) and two reduced splint me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(69 citation statements)
references
References 34 publications
4
62
0
3
Order By: Relevance
“…the merging of DI with DII, and DIV with DV), clearly showing that cell lineages from all five metacarpals persist in the older horse FL and that DI and DV are not absent or solely carved away as previously thought, but rather they also fuse at this stage (figure 2a,b,e,f,i,j; electronic supplementary material, figures S1 and S3). This observation is in agreement with the recent palaeontological hypothesis that remnants of all five digits persist in adult Equus metacarpals [6]. More proximally, all condensations join at the carpal-metacarpal joint and are hard to distinguish (electronic supplementary material, figures S1 and S3).…”
Section: (A) Forelimbssupporting
confidence: 91%
See 1 more Smart Citation
“…the merging of DI with DII, and DIV with DV), clearly showing that cell lineages from all five metacarpals persist in the older horse FL and that DI and DV are not absent or solely carved away as previously thought, but rather they also fuse at this stage (figure 2a,b,e,f,i,j; electronic supplementary material, figures S1 and S3). This observation is in agreement with the recent palaeontological hypothesis that remnants of all five digits persist in adult Equus metacarpals [6]. More proximally, all condensations join at the carpal-metacarpal joint and are hard to distinguish (electronic supplementary material, figures S1 and S3).…”
Section: (A) Forelimbssupporting
confidence: 91%
“…Nevertheless, this limited data on horse embryology suggested that horses only ever form three digit remnants during their development and became an important cornerstone of the general view of the evolutionary developmental biology of digits [8][9][10]. By contrast, a recent palaeontology paper proposed a novel hypothesis, based on bone articulations and ridges in fossil horses and vasculature in late foetal horses, that the identities of all five ancestral digits might be preserved in the metacarpal anatomy of the modern horse adult FL [6], but direct evidence was lacking. This same study also proposed that the horse 'frog' (distal hoof cartilage) is a distal remnant of all five digit condensations, although embryological evidence was again lacking.…”
Section: Introductionmentioning
confidence: 99%
“…During the same epoch, the perissodactyl forebears of Equidae , the tridactyl Mesohippus and Merychippus had anatomic structures comparable to the Acrocodia indica (Malayan tapir), including interosseous muscles [38]. The three digits in the tridactyl were referred to as II, III and IV (medial, middle and lateral respectively), with III being the largest, widest and dominant during weightbearing [38,39]. Each interosseous muscle corresponded to its metacarpal or metatarsal; hence, the interosseous muscles in the Mesohippus and Merychippus would be labelled IM2, IM3 and IM4 from which they originated [12,15].…”
Section: Discussionmentioning
confidence: 99%
“…During the same epoch, the perissodactyl forebears of Equidae, the tridactyl Mesohippus and Merychippus had anatomic structures comparable to the tapir, including interosseous muscles [36]. The 3 digits in the tridactyl were referred to as II, III and IV (medial, middle and lateral respectively), with III being the largest, widest and dominant during weightbearing [36,37]. Each interosseous muscle corresponded to its metacarpal or metatarsal, hence the interosseous muscles in the Mesohippus and Merychippus would be labelled IM2, IM3 and IM4 from which they originated [12,15].…”
Section: Discussionmentioning
confidence: 99%